Does tocilizumab eliminate inflammation in GCA? A cohort study on repeated temporal artery biopsies - Chiara Marvisi; Francesco Muratore; Carlo Salvarani; Pierluigi Macchioni; Pamela Mancuso; Luigi Boiardi; Stefania Croci; Paolo Giorgi Rossi; Alberto Cavazza; Annibale Versari; Rexhep Durmo; Caterina Ricordi; et al. (RMD Open)
Background Vascular inflammation persists in temporal artery biopsy (TAB) of giant cell arteritis (GCA) patients even after prolonged glucocorticoid (GC) therapy. We aimed to evaluate the histological impact of adding tocilizumab (TCZ) to GCs.Methods We enrolled all consecutive GCA patients with an inflammed TAB at diagnosis who were treated with TCZ and GCs for ≥6 months and followed from December 2017 to December 2023. Within 2 weeks, all patients underwent a second TAB, positron emission 18-fluorodeoxyglucose tomography/CT (PET/CT) and vessel colour Doppler ultrasonography (CDUS). Results were compared with pretreatment findings.Results 13 patients repeated TAB after a median TCZ treatment of 2.4 years (Q1–Q3: 1.2–3.9 years). The first TAB showed transmural inflammation (TMI) in 11/13 patients (84.6%), inflammation limited to adventitia (ILA) in one patient (7.7%) and small vessel vasculitis (SVV) in another (7.7%). On repeated TABs, five patients (38.5%) still showed some degree of inflammation. Among the 11 patients with initial TMI, 2 had ILA, 1 had TMI, 1had SVV and 1 had vasa vasorum vasculitis at the second TAB. Nine patients had active vasculitis at baseline PET/CT, and three (33.3%) still showed activity at the last PET/CT, with a relevant reduction in mean PET vascular activity score (−6.5; 95% CI 1.54 to 11.45; p=0.017). The repeated quantitative CDUS revealed altered parameters suggestive of vasculitis in temporal arteries in about one-third of the patients.Conclusion Our study, using pathological and imaging assessments, revealed that after TCZ and GCs, over one-third of patients still presented with vascular inflammation.